2017
DOI: 10.1089/gyn.2016.0101
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Laparoscopy and Laparotomy in Systematic Para-Aortic Lymphadenectomy for Patients with Endometrial Cancer: A Retrospective Multicenter Study

Abstract: Objective: Laparoscopic surgery has been developed worldwide due to its minimal invasion as well as noninferiority, compared with laparotomy. However, whether or not laparoscopic systematic para-aortic lymphadenectomy for endometrial cancer is feasible and has advantages of various clinical factors, such as a short hospital stay, less blood loss, and faster recovery, compared with open surgery has not yet been clarified. The aim of this study was to compare a laparoscopic procedure with laparotomy for para-aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…19 The status of both the pelvic and paraaortic lymph nodes should be assessed intraoperatively in intermediate/high risk of recurrence patients, as advised by the FIGO surgical and pathologic staging system. 20 However, the type and extent of LND were not specified.…”
Section: Discussionmentioning
confidence: 99%
“…19 The status of both the pelvic and paraaortic lymph nodes should be assessed intraoperatively in intermediate/high risk of recurrence patients, as advised by the FIGO surgical and pathologic staging system. 20 However, the type and extent of LND were not specified.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of minimally invasive methods, surgery for endometrial cancer has evolved substantially in recent decades 3 . One of the major advancements was the change from open surgery to laparoscopic surgery that occurred in the late 1990s and that resulted in lower perioperative morbidity without losing the radicality or effectiveness of oncological surgery 4 - 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, data on the recurrence rate of laparoscopic surgery are limited, and only one study has reported its short-term operative outcomes such as the amount of blood loss, operative time, and complications. [ 7 8 ] In fact, recently, the high recurrence rate of cervical and endometrial cancers following minimally invasive procedures is frequently reported. [ 9 10 ] Accumulating Japanese domestic data on the outcomes of laparoscopic surgery for endometrial cancer is necessary, especially on the long-term recurrence risk and the recurrence risk factors.…”
Section: Introductionmentioning
confidence: 99%